Boron nitride composite coating for melting and casting equipment and preparation method thereof
By adding a variety of components to the boron nitride coating, the wear resistance and corrosion resistance of the coating are improved, and the problem of poor performance of existing coatings in high temperature environments is solved, achieving higher service life and production efficiency.
Patent Information
- Application Number
- CN202411549802.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The existing boron nitride coatings have poor wear resistance and corrosion resistance in high temperature environments, making it difficult to meet the requirements of high-performance alloy casting.
Composite coatings with boron nitride as the main material are improved by preparing multi-components such as alumina, zirconium silicate, silicon carbide, polytetrafluoroethylene, silicon oil, aluminum borate whiskers, nanosilica, alumina fibers, yttrium oxide and other multi-components, and a reasonable composition distribution ratio and preparation process are used to improve the overall performance of the coating.
The coating is achieved with high adhesion, strength, high temperature resistance and excellent wear and corrosion resistance, extending service life and reducing production costs.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-temperature coatings, and in particular relates to a boron nitride composite coating for melting and casting equipment and a preparation method thereof. Background Art
[0002] With the development of modern industry, especially in the fields of melting, forging and powder metallurgy of aluminum, magnesium, zinc and other alloys, higher requirements are put forward for the protection of refractory materials and molds in high temperature environments. Especially for high-performance metal materials, such as those used in the production of electronic products, aerospace and automotive parts, it is necessary to prevent molds or utensils from contaminating molten metal in high temperature environments. Traditional coatings are prone to failure at high temperatures, resulting in increased corrosion and wear of equipment, and it is difficult to effectively prevent the penetration and contamination of molten metal. Take talcum powder as an example. Talc powder is often used as an aggregate in coatings, especially in aluminum alloy sand mold low-pressure casting. Talc powder is mixed with titanium dioxide, clay, etc. to make alcohol-based casting coatings. Talc powder has good lubricity, which helps fill the molten metal and reduce casting defects. However, the molecular formula of talcum powder is Mg3Si4O 10 (0H)2, which will decompose H2O at 600℃, increasing the hydrogen content of the aluminum rod, which will affect the quality of the profiles produced by the aluminum rod to a certain extent.
[0003] For this reason, boron nitride coatings have been developed in the field of metal and alloy casting, which have good high-temperature lubricity, chemical inertness and acid and alkali resistance, do not wet molten metal, and can protect the surface of refractory materials or ceramic vessels that are in direct contact with molten aluminum, magnesium, copper, zinc alloys and slag, thereby extending the service life of such vessels. Chinese invention patent CN109848364A discloses a boron nitride coating for pressure casting and a preparation method thereof, which can have good high-temperature lubricity and surface strength of the coating when used in the field of pressure casting, but its formula is simple, and its wear resistance and corrosion resistance are not strong, and the overall performance of the coating cannot meet the requirements of current high-performance alloy casting. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a boron nitride composite coating for melting and casting equipment and a preparation method thereof.
[0005] The invention provides a boron nitride composite coating for melting and casting equipment, which comprises, by weight, 100-300 parts of boron nitride, 50-100 parts of aluminum oxide, 30-50 parts of zirconium silicate, 20-40 parts of silicon carbide, 5-20 parts of polytetrafluoroethylene, 50-80 parts of silicone oil, 20-40 parts of aluminum borate whiskers, 10-20 parts of nano silicon dioxide, 10-20 parts of aluminum oxide fibers, 5-10 parts of yttrium oxide, 1-5 parts of dispersant, 1-3 parts of coupling agent and 200-400 parts of deionized water.
[0006] Furthermore, in parts by weight, it includes: 100-200 parts of boron nitride, 50-80 parts of aluminum oxide, 30-45 parts of zirconium silicate, 20-35 parts of silicon carbide, 5-15 parts of polytetrafluoroethylene, 50-70 parts of silicone oil, 20-35 parts of aluminum borate whiskers, 10-18 parts of nano-silicon dioxide, 10-18 parts of aluminum oxide fibers, 5-8 parts of yttrium oxide, 1-5 parts of dispersant, 1-3 parts of coupling agent, and 200-300 parts of deionized water.
[0007] Furthermore, in parts by weight, it includes: 150-200 parts of boron nitride, 60-80 parts of aluminum oxide, 35-45 parts of zirconium silicate, 25-35 parts of silicon carbide, 10-15 parts of polytetrafluoroethylene, 60-70 parts of silicone oil, 25-35 parts of aluminum borate whiskers, 15-18 parts of nano-silicon dioxide, 15-18 parts of aluminum oxide fibers, 7-8 parts of yttrium oxide, 1-5 parts of dispersant, 1-3 parts of coupling agent, and 250-300 parts of deionized water.
[0008] Furthermore, the invention further comprises, by weight: 1-5 parts of rare earth oxide, wherein the rare earth oxide is one of lanthanum oxide and cerium oxide.
[0009] Furthermore, in parts by weight, it also includes: 1-3 parts of boron carbide.
[0010] Furthermore, the dispersant is one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, and sodium polyacrylate.
[0011] Furthermore, the coupling agent is one of a silane coupling agent, a titanate coupling agent and an aluminate coupling agent.
[0012] The present invention also provides a method for preparing the above-mentioned boron nitride composite coating for melting and casting equipment, comprising the following steps:
[0013] Step S1: mixing solid powders evenly according to a proportion, and grinding the mixed solid powders;
[0014] Step S2: adding silicone oil, dispersant, coupling agent and deionized water into a stirrer for stirring at a speed of 250 r / min, gradually adding the solid powder after the grinding treatment in step S1 into the stirrer, and in the process of adding the solid powder, increasing the stirring speed of the stirrer by 250 r / min every 10 minutes, and controlling the maximum stirring speed to 2200-2400 r / min, stirring for 2-3 hours at the maximum stirring speed;
[0015] Step S3: let the slurry after stirring stand for 10-14 hours and then discharge it.
[0016] Furthermore, in step S1, the solid powder is ground to a particle size of 5-10 μm.
[0017] Furthermore, in step S3, the solid content of the discharged boron nitride composite coating is 25-30%.
[0018] The boron nitride composite coating of the present invention has at least the following beneficial effects:
[0019] 1. It has good non-wetting properties to molten aluminum, copper, magnesium, zinc and their alloys, which can effectively protect the refractory materials in contact with the molten metal, enhance corrosion resistance, extend its service life, improve production efficiency and reduce production costs.
[0020] 2. The coating has good adhesion, high strength, good thermal stability, excellent high temperature resistance, can remain stable in high temperature environment, and has a long service life;
[0021] 3. The composite boron nitride composite coating has excellent wear resistance and corrosion resistance as well as good high-temperature lubricity, which can reduce the friction and wear between the molten metal and the equipment and has excellent demoulding effect;
[0022] 4. The boron nitride composite coating of the present invention has a reasonable component ratio, and the components work synergistically to improve the overall performance of the coating. The preparation process is simple and suitable for industrial production applications. DETAILED DESCRIPTION
[0023] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0024] During the casting process of aluminum, magnesium, zinc and other metals and their alloys, they flow or cool in the form of molten metal in the mold, runner, chute or casting plate and other equipment. After the casting is completed, the residual molten metal will cool and solidify in the above equipment and bond with it. At this time, the operator needs to manually clean the residual metal blocks from the equipment. During the cleaning process, the paint on the surface of the equipment often falls off and is damaged. At this time, the surface of the equipment needs to be coated again to ensure that other substances in the equipment will not enter the molten metal during the next casting, causing pollution to the casting and demolding effect. Traditional talcum powder can often only be used for one furnace after coating. After that, the protective layer fails and powdering is serious. During the casting process, talcum powder is easily involved in aluminum liquid due to the erosion of metal liquid, causing impurities; while the overall performance of the current boron nitride coating is not good, the service life is not long enough, and the production cost is high.
[0025] An embodiment of the present invention provides a boron nitride composite coating for melting and casting equipment, which includes, by weight: 100-300 parts of boron nitride, 50-100 parts of aluminum oxide, 30-50 parts of zirconium silicate, 20-40 parts of silicon carbide, 5-20 parts of polytetrafluoroethylene, 50-80 parts of silicone oil, 20-40 parts of aluminum borate whiskers, 10-20 parts of nano-silicon dioxide, 10-20 parts of aluminum oxide fibers, 5-10 parts of yttrium oxide, 1-5 parts of dispersant, 1-3 parts of coupling agent, and 200-400 parts of deionized water.
[0026] Furthermore, in parts by weight, it includes: 100-200 parts of boron nitride, 50-80 parts of aluminum oxide, 30-45 parts of zirconium silicate, 20-35 parts of silicon carbide, 5-15 parts of polytetrafluoroethylene, 50-70 parts of silicone oil, 20-35 parts of aluminum borate whiskers, 10-18 parts of nano-silicon dioxide, 10-18 parts of aluminum oxide fibers, 5-8 parts of yttrium oxide, 1-5 parts of dispersant, 1-3 parts of coupling agent, and 200-300 parts of deionized water.
[0027] Furthermore, in parts by weight, it includes: 150-200 parts of boron nitride, 60-80 parts of aluminum oxide, 35-45 parts of zirconium silicate, 25-35 parts of silicon carbide, 10-15 parts of polytetrafluoroethylene, 60-70 parts of silicone oil, 25-35 parts of aluminum borate whiskers, 15-18 parts of nano-silicon dioxide, 15-18 parts of aluminum oxide fibers, 7-8 parts of yttrium oxide, 1-5 parts of dispersant, 1-3 parts of coupling agent, and 250-300 parts of deionized water.
[0028] The boron nitride composite coating provided by the present invention is based on boron nitride as the main material, and the composite multi-component is matched with boron nitride, the component ratio is reasonable, and the components cooperate with each other to improve the overall performance of the coating. Boron nitride is used as the main material, and its friction coefficient is low, and its self-lubricating performance is excellent. In particular, it still has a good lubricating effect at high temperature, providing the main high-temperature lubrication performance and wear resistance. Alumina has high hardness and corrosion resistance. Compounding alumina into boron nitride coating can significantly improve the hardness and wear resistance of the coating, and extend the service life of the coating. Its corrosion resistance can resist the erosion of various chemical substances. In addition, the alumina particles are small and uniform, and can fill the tiny bumps on the surface of the coating, making the coating surface smoother and improving the gloss and flatness of the coating. Alumina fiber can improve the hardness of the coating, and also has excellent chemical stability and heat resistance, maintaining the performance of the coating stable under high temperature conditions, and extending the service life of the coating. The high hardness and chemical stability of zirconium silicate can improve the thermal shock resistance and wear resistance of the coating. At the same time, zirconium silicate can adjust the fluidity and viscosity of the coating, reduce the construction difficulty of the coating and improve the coating efficiency. Nano-silicon dioxide is used to enhance the density and wear resistance of coatings. Silicon carbide can effectively improve the hardness and wear resistance of coatings, effectively resist friction and wear, and extend the service life of coatings; secondly, silicon carbide has good corrosion resistance and oxidation resistance, and can protect coatings from chemical erosion and oxidation at high temperatures. Aluminum borate whiskers are often used as reinforcing materials for plastics, metals, and ceramics due to their stable performance and superior mechanical properties. In the scheme of the present invention, the refractoriness and corrosion resistance of coatings can be increased by adding aluminum borate whiskers. Yttrium oxide is mainly used as a stabilizer in composite coatings to improve the chemical stability of coatings; polytetrafluoroethylene is mainly used to improve the lubrication and non-stickiness of coatings; silicone oil is used as a solvent and lubricant; dispersants are used to improve the dispersibility of powders when preparing coatings, and coupling agents are used to enhance the bonding between powders and substrates. The multi-component composite boron nitride coating has excellent comprehensive properties. When applied to the melting and casting process, it can provide excellent high temperature resistance, wear resistance and corrosion resistance. The formed coating has high strength and long service life. At the same time, it has good high-temperature lubricity, which reduces the friction between the molten metal and the equipment during the flow process, protects the refractory materials in contact with the molten metal, and prolongs its service life.
[0029] Furthermore, the invention further comprises, by weight, 1-5 parts of rare earth oxide, wherein the rare earth oxide is one of lanthanum oxide and cerium oxide. Rare earth oxide as an auxiliary material also has multiple functions. First, it can be used as a curing agent to enhance the curing effect of the coating, increase the adhesion of the coating to the coated equipment, and is not easy to fall off after multiple uses; secondly, it can improve the oxidation resistance and stability of the coating, and maintain the stability of the coating in a high temperature environment.
[0030] Furthermore, in parts by weight, it also includes: 1-3 parts of boron carbide, which is a special ceramic material. In industry, it is mainly used in the manufacture of wear-resistant materials, cutting tools, bearings and other fields; in the aerospace field, it is mainly used to manufacture lightweight structural parts and composite materials, etc. The boron nitride composite coating of the present invention innovatively adds boron carbide as an important auxiliary material, which can further improve the hardness and wear resistance of the coating.
[0031] Further, the dispersant is one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, and sodium polyacrylate. Boron nitride particles are often difficult to disperse evenly in the coating due to their high surface energy and easy agglomeration characteristics, which affects the performance of the coating. In this scheme, multiple components are compounded, and the dispersion effect of the powder in the solvent has a particularly obvious effect on the performance of the coating, so a dispersant is needed to promote the dispersion of the powder. Sodium dodecylbenzene sulfonate has excellent dispersibility and wetting properties. During the mixing process, the sodium dodecylbenzene sulfonate molecules will be adsorbed on the surface of the powder particles to form a stable negative ion film, thereby preventing the agglomeration between particles. Sodium dodecyl sulfate also has good dispersibility and wetting properties, but the addition amount of sodium dodecyl sulfate needs to be strictly controlled to avoid adverse effects on other properties of the coating. Sodium polyacrylate has good dispersibility and can be effectively adsorbed on the surface of the particles in the composite coating to form a stable hydration film, organize the agglomeration between the particles, thereby improving the dispersion uniformity of the coating; in addition, sodium polyacrylate can also increase the viscosity of the coating, improve its rheological properties, and make the construction of the coating smoother.
[0032] Furthermore, the coupling agent is one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent. The molecular structure of the silane coupling agent contains a siloxane group that can react with the hydroxyl group on the surface of boron nitride. In the boron nitride composite coating, the silane coupling agent can tightly connect the boron nitride particles with other components through chemical bonding, thereby improving the adhesion and durability of the coating. The titanate coupling agent contains a titanate group in its molecular structure, which can react with the hydroxyl group on the surface of the boron nitride particles to form a stable chemical bond. The aluminate coupling agent has excellent dispersibility and stability. In the boron nitride composite coating, the aluminate coupling agent can effectively disperse the boron nitride particles in the coating system and form a good bond with other components.
[0033] The present invention also provides a method for preparing the above-mentioned boron nitride composite coating for melting and casting equipment, comprising the following steps:
[0034] Step S1: mixing solid powders evenly according to a proportion, and grinding the mixed solid powders;
[0035] Step S2: adding silicone oil, dispersant, coupling agent and deionized water into a stirrer for stirring at a speed of 250 r / min, gradually adding the solid powder after the grinding treatment in step S1 into the stirrer, and in the process of adding the solid powder, increasing the stirring speed of the stirrer by 250 r / min every 10 minutes, and controlling the maximum stirring speed to 2200-2400 r / min, stirring for 2-3 hours at the maximum stirring speed;
[0036] Step S3: let the slurry after stirring stand for 10-14 hours and then discharge it.
[0037] Furthermore, in step S1, the solid powder is ground to a particle size of 5-10 μm.
[0038] Furthermore, in step S3, the solid content of the discharged boron nitride composite coating is 25-30%.
[0039] To better illustrate the solutions of the present invention, the following are specific embodiments.
[0040] Example 1
[0041] The proportion of the boron nitride composite coating is as follows: in parts by weight, it includes: 100 parts of boron nitride, 50 parts of aluminum oxide, 30 parts of zirconium silicate, 20 parts of silicon carbide, 5 parts of polytetrafluoroethylene, 50 parts of silicone oil, 20 parts of aluminum borate whiskers, 10 parts of nano-silica, 10 parts of aluminum oxide fiber, 5 parts of yttrium oxide, 2 parts of sodium dodecylbenzene sulfonate, 1 part of aluminate coupling agent, and 200 parts of deionized water.
[0042] Preparation method:
[0043] The solid powder is mixed evenly according to a proportion, and the mixed solid powder is ground;
[0044] Add silicone oil, dispersant, coupling agent and deionized water into a stirrer and stir at a stirring speed of 250 r / min. Gradually add the solid powder after grinding in step S1 into the stirrer. During the process of adding the solid powder, increase the stirring speed of the stirrer by 250 r / min every 10 minutes, and control the maximum stirring speed to 2200-2400 r / min. Stir for 2-3 hours at the maximum stirring speed.
[0045] The stirred slurry is allowed to stand for 10-14 hours before being discharged.
[0046] Example 2
[0047] The ratio of boron nitride composite coating is as follows: in parts by weight, including: 150 parts of boron nitride, 60 parts of aluminum oxide, 35 parts of zirconium silicate, 30 parts of silicon carbide, 8 parts of polytetrafluoroethylene, 60 parts of silicone oil, 25 parts of aluminum borate whiskers, 14 parts of nano-silica, 14 parts of alumina fiber, 6 parts of yttrium oxide, 2 parts of sodium dodecylbenzene sulfonate, 2 parts of aluminate coupling agent, and 280 parts of deionized water.
[0048] Preparation method:
[0049] The solid powder is mixed evenly according to a proportion, and the mixed solid powder is ground;
[0050] Add silicone oil, dispersant, coupling agent and deionized water into a stirrer and stir at a stirring speed of 250 r / min. Gradually add the solid powder after grinding in step S1 into the stirrer. During the process of adding the solid powder, increase the stirring speed of the stirrer by 250 r / min every 10 minutes, and control the maximum stirring speed to 2200-2400 r / min. Stir for 2-3 hours at the maximum stirring speed.
[0051] The stirred slurry is allowed to stand for 10-14 hours before being discharged.
[0052] Example 3
[0053] The ratio of boron nitride composite coating is as follows: in parts by weight, including: 200 parts of boron nitride, 80 parts of aluminum oxide, 40 parts of zirconium silicate, 30 parts of silicon carbide, 12 parts of polytetrafluoroethylene, 70 parts of silicone oil, 30 parts of aluminum borate whiskers, 18 parts of nano-silica, 18 parts of alumina fiber, 8 parts of yttrium oxide, 3 parts of sodium dodecylbenzene sulfonate, 2 parts of aluminate coupling agent, and 300 parts of deionized water.
[0054] Preparation method:
[0055] The solid powder is mixed evenly according to a proportion, and the mixed solid powder is ground;
[0056] Add silicone oil, dispersant, coupling agent and deionized water into a stirrer and stir at a stirring speed of 250 r / min. Gradually add the solid powder after grinding in step S1 into the stirrer. During the process of adding the solid powder, increase the stirring speed of the stirrer by 250 r / min every 10 minutes, and control the maximum stirring speed to 2200-2400 r / min. Stir for 2-3 hours at the maximum stirring speed.
[0057] The stirred slurry is allowed to stand for 10-14 hours before being discharged.
[0058] Example 4
[0059] The ratio of boron nitride composite coating is as follows: in parts by weight, including: 250 parts of boron nitride, 85 parts of aluminum oxide, 45 parts of zirconium silicate, 35 parts of silicon carbide, 18 parts of polytetrafluoroethylene, 75 parts of silicone oil, 35 parts of aluminum borate whiskers, 18 parts of nano-silica, 18 parts of alumina fiber, 8 parts of yttrium oxide, 4 parts of sodium dodecylbenzene sulfonate, 2 parts of aluminate coupling agent, and 350 parts of deionized water.
[0060] Preparation method:
[0061] The solid powder is mixed evenly according to a proportion, and the mixed solid powder is ground;
[0062] Add silicone oil, dispersant, coupling agent and deionized water into a stirrer and stir at a stirring speed of 250 r / min. Gradually add the solid powder after grinding in step S1 into the stirrer. During the process of adding the solid powder, increase the stirring speed of the stirrer by 250 r / min every 10 minutes, and control the maximum stirring speed to 2200-2400 r / min. Stir for 2-3 hours at the maximum stirring speed.
[0063] The stirred slurry is allowed to stand for 10-14 hours before being discharged.
[0064] Example 5
[0065] The ratio of boron nitride composite coating is as follows: in parts by weight, including: 300 parts of boron nitride, 100 parts of aluminum oxide, 50 parts of zirconium silicate, 40 parts of silicon carbide, 20 parts of polytetrafluoroethylene, 80 parts of silicone oil, 40 parts of aluminum borate whiskers, 20 parts of nano-silica, 20 parts of alumina fiber, 10 parts of yttrium oxide, 5 parts of sodium dodecylbenzene sulfonate, 3 parts of aluminate coupling agent, and 400 parts of deionized water.
[0066] Preparation method:
[0067] The solid powder is mixed evenly according to a proportion, and the mixed solid powder is ground;
[0068] Add silicone oil, dispersant, coupling agent and deionized water into a stirrer and stir at a stirring speed of 250 r / min. Gradually add the solid powder after grinding in step S1 into the stirrer. During the process of adding the solid powder, increase the stirring speed of the stirrer by 250 r / min every 10 minutes, and control the maximum stirring speed to 2200-2400 r / min. Stir for 2-3 hours at the maximum stirring speed.
[0069] The stirred slurry is allowed to stand for 10-14 hours before being discharged.
[0070] Example 6
[0071] The proportion of the boron nitride composite coating is as follows: in parts by weight, it includes: 100 parts of boron nitride, 50 parts of aluminum oxide, 30 parts of zirconium silicate, 20 parts of silicon carbide, 5 parts of polytetrafluoroethylene, 50 parts of silicone oil, 20 parts of aluminum borate whiskers, 10 parts of nano-silica, 10 parts of aluminum oxide fiber, 5 parts of yttrium oxide, 1 part of lanthanum oxide, 2 parts of sodium dodecylbenzene sulfonate, 1 part of aluminate coupling agent, and 200 parts of deionized water.
[0072] Preparation method:
[0073] The solid powder is mixed evenly according to a proportion, and the mixed solid powder is ground;
[0074] Add silicone oil, dispersant, coupling agent and deionized water into a stirrer and stir at a stirring speed of 250 r / min. Gradually add the solid powder after grinding in step S1 into the stirrer. During the process of adding the solid powder, increase the stirring speed of the stirrer by 250 r / min every 10 minutes, and control the maximum stirring speed to 2200-2400 r / min. Stir for 2-3 hours at the maximum stirring speed.
[0075] The stirred slurry is allowed to stand for 10-14 hours before being discharged.
[0076] Example 7
[0077] The proportion of the boron nitride composite coating is as follows: in parts by weight, it includes: 100 parts of boron nitride, 50 parts of aluminum oxide, 30 parts of zirconium silicate, 20 parts of silicon carbide, 5 parts of polytetrafluoroethylene, 50 parts of silicone oil, 20 parts of aluminum borate whiskers, 10 parts of nano-silica, 10 parts of aluminum oxide fiber, 5 parts of yttrium oxide, 1 part of boron carbide, 2 parts of sodium dodecylbenzene sulfonate, 1 part of aluminate coupling agent, and 200 parts of deionized water.
[0078] Preparation method:
[0079] The solid powder is mixed evenly according to a proportion, and the mixed solid powder is ground;
[0080] Add silicone oil, dispersant, coupling agent and deionized water into a stirrer and stir at a stirring speed of 250 r / min. Gradually add the solid powder after grinding in step S1 into the stirrer. During the process of adding the solid powder, increase the stirring speed of the stirrer by 250 r / min every 10 minutes, and control the maximum stirring speed to 2200-2400 r / min. Stir for 2-3 hours at the maximum stirring speed.
[0081] The stirred slurry is allowed to stand for 10-14 hours before being discharged.
[0082] Example 8
[0083] The proportion of the boron nitride composite coating is as follows: in parts by weight, it includes: 100 parts of boron nitride, 50 parts of aluminum oxide, 30 parts of zirconium silicate, 20 parts of silicon carbide, 5 parts of polytetrafluoroethylene, 50 parts of silicone oil, 20 parts of aluminum borate whiskers, 10 parts of nano-silicon dioxide, 10 parts of aluminum oxide fiber, 5 parts of yttrium oxide, 1 part of lanthanum oxide, 1 part of boron carbide, 2 parts of sodium dodecylbenzene sulfonate, 1 part of aluminate coupling agent, and 200 parts of deionized water.
[0084] Preparation method:
[0085] The solid powder is mixed evenly according to a proportion, and the mixed solid powder is ground;
[0086] Add silicone oil, dispersant, coupling agent and deionized water into a stirrer and stir at a stirring speed of 250 r / min. Gradually add the solid powder after grinding in step S1 into the stirrer. During the process of adding the solid powder, increase the stirring speed of the stirrer by 250 r / min every 10 minutes, and control the maximum stirring speed to 2200-2400 r / min. Stir for 2-3 hours at the maximum stirring speed.
[0087] The stirred slurry is allowed to stand for 10-14 hours before being discharged.
[0088] Comparative Example 1
[0089] The difference from Example 1 is that no boron nitride is added.
[0090] Comparative Example 2
[0091] The difference from Example 1 is that zirconium silicate is not added.
[0092] Comparative Example 3
[0093] The difference from Example 1 is that no alumina was added.
[0094] Comparative Example 4
[0095] The difference from Example 1 is that silicon carbide is not added.
[0096] Comparative Example 5
[0097] The difference from Example 1 is that no aluminum borate whiskers are added.
[0098] Comparative Example 6
[0099] The difference from Example 1 is that sodium dodecylbenzene sulfonate was not added.
[0100] Comparative Example 7
[0101] The difference from Example 1 is that no aluminate coupling agent is added.
[0102] Comparative Example 8
[0103] The difference from Example 8 is that no boron nitride is added.
[0104] The coatings prepared in Examples 1-8 and Comparative Examples 1-8 were subjected to surface coating friction coefficient (ISO 22462:2020), coating hardness (GB / T 6739-2022), adhesion (GB / T 5210-2006), and non-stick aluminum tests (simulating the production environment, brushing the coating evenly onto the surface and sides of the flow channel, and then baking it with a torch for about 5 minutes to make the flow channel reach about 120 degrees, and then letting the molten aluminum flow through the flow channel to observe the flow channel condition). The following are the specific test results.
[0105] Table 1 Test results
[0106]
[0107] From the above test results, it can be seen that Examples 1 to 5 illustrate that the coating formed by the boron nitride composite coating of this scheme has excellent adhesion and strength, low friction coefficient and good non-wetting properties with metal materials. Compared with Example 1, Example 6 adds rare earth metal oxide (lanthanum oxide), and it can be seen that the adhesion performance of Example 6 is significantly improved; Compared with Example 1, Example 7 adds boron carbide, and it can be seen that the hardness of Example 7 is significantly improved; Compared with Example 1, Example 8 adds lanthanum oxide and boron carbide, and its adhesion and hardness are significantly improved.
[0108] Compared with Examples 1 and 8, Comparative Examples 1 and 8 do not add boron nitride. It can be seen that without the addition of boron nitride, the comprehensive performance of the coating is significantly reduced and cannot meet the use requirements; Comparative Example 2 does not add zirconium silicate relative to Example 1, and its adhesion is significantly reduced; Comparative Example 3 does not add aluminum oxide relative to Example 1, and its friction coefficient increases and its hardness decreases; Comparative Example 4 has a slight decrease in strength relative to Example 1; Comparative Example 5 does not add aluminum borate whiskers relative to Example 1, and its strength is slightly reduced; Comparative Examples 6 and 7 do not add dispersants and coupling agents relative to Example 1, and it can be seen that the friction coefficient of the coating increases, and the hardness and adhesion are reduced.
[0109] In order to further illustrate the effect of the boron nitride composite coating of the present scheme, a comparative test of the maintenance chute of aluminum casting was carried out using the boron nitride coating prepared in Example 1 and talcum powder.
[0110] Trial plan
[0111] 1. Use sandpaper to thoroughly clean the residual impurities on the flow trough and casting plate, blow them clean with an air pipe, and evenly brush the boron nitride composite coating and talcum powder diluted with water according to the use requirements onto the surface and sides of the flow trough and casting plate, and then bake them with a torch for about 5 minutes to make the flow trough reach about 120 degrees; then proceed with aluminum alloy production casting.
[0112] 2. Determine the re-maintenance standard:
[0113] 1) It is difficult to pick up aluminum;
[0114] 2) The protective layer fails and the flow channel bottoms out;
[0115] 3) Severe powdering or flaking.
[0116] Test results
[0117]
[0118] The test results show that when talcum powder is used to maintain the chute, maintenance is required again after completing one batch of production, while when boron nitride composite coating is used to maintain the chute, three batches of production can be completed. When maintenance is required again: the chute using boron nitride composite coating is easy to pick up aluminum, and only part of the coating protective layer fails; the chute using talcum powder is easy to pick up aluminum, but the protective layer fails, powdering is serious, and part of the chute bottoms out. It can be seen that the boron nitride composite coating of this scheme has good high-temperature lubricity, adhesion performance and service life compared to traditional talcum powder, which reduces the labor intensity and cost of operators and improves production efficiency.
[0119] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A boron nitride composite coating for melting and casting equipment, characterized in that: The invention comprises, by weight, 100-300 parts of boron nitride, 50-100 parts of aluminum oxide, 30-50 parts of zirconium silicate, 20-40 parts of silicon carbide, 5-20 parts of polytetrafluoroethylene, 50-80 parts of silicone oil, 20-40 parts of aluminum borate whiskers, 10-20 parts of nano-silicon dioxide, 10-20 parts of aluminum oxide fibers, 5-10 parts of yttrium oxide, 1-5 parts of dispersant, 1-3 parts of coupling agent, 200-400 parts of deionized water, 1-3 parts of boron carbide and 1-5 parts of rare earth oxide; the rare earth oxide is one of lanthanum oxide and cerium oxide.
2. The boron nitride composite coating for melting and casting equipment according to claim 1, characterized in that: The invention comprises, by weight, 100-200 parts of boron nitride, 50-80 parts of aluminum oxide, 30-45 parts of zirconium silicate, 20-35 parts of silicon carbide, 5-15 parts of polytetrafluoroethylene, 50-70 parts of silicone oil, 20-35 parts of aluminum borate whiskers, 10-18 parts of nano-silicon dioxide, 10-18 parts of aluminum oxide fibers, 5-8 parts of yttrium oxide, 1-5 parts of dispersant, 1-3 parts of coupling agent, 200-300 parts of deionized water, 1-3 parts of boron carbide and 1-5 parts of rare earth oxide; the rare earth oxide is one of lanthanum oxide and cerium oxide.
3. The boron nitride composite coating for melting and casting equipment according to claim 2, characterized in that: The invention comprises, by weight, 150-200 parts of boron nitride, 60-80 parts of aluminum oxide, 35-45 parts of zirconium silicate, 25-35 parts of silicon carbide, 10-15 parts of polytetrafluoroethylene, 60-70 parts of silicone oil, 25-35 parts of aluminum borate whiskers, 15-18 parts of nano-silicon dioxide, 15-18 parts of aluminum oxide fibers, 7-8 parts of yttrium oxide, 1-5 parts of dispersant, 1-3 parts of coupling agent, 250-300 parts of deionized water, 1-3 parts of boron carbide and 1-5 parts of rare earth oxide; the rare earth oxide is one of lanthanum oxide and cerium oxide.
4. The boron nitride composite coating for melting and casting equipment according to claim 1, characterized in that: The dispersant is one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and sodium polyacrylate.
5. The boron nitride composite coating for melting and casting equipment according to claim 1, characterized in that: The coupling agent is one of a silane coupling agent, a titanate coupling agent and an aluminate coupling agent.
6. A method for preparing a boron nitride composite coating for melting and casting equipment according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step S1: mixing solid powders evenly according to a proportion, and grinding the mixed solid powders; Step S2: adding silicone oil, dispersant, coupling agent and deionized water into a stirrer for stirring at a speed of 250 r / min, gradually adding the solid powder after the grinding treatment in step S1 into the stirrer, and in the process of adding the solid powder, increasing the stirring speed of the stirrer by 250 r / min every 10 minutes, and controlling the maximum stirring speed to 2200-2400 r / min, stirring for 2-3 hours at the maximum stirring speed; Step S3: let the slurry after stirring stand for 10-14 hours and then discharge it.
7. The method for preparing the boron nitride composite coating for melting and casting equipment according to claim 6, characterized in that: In step S1, the solid powder is ground to a particle size of 5-10 μm.
8. The method for preparing the boron nitride composite coating for melting and casting equipment according to claim 6, characterized in that: In step S3, the solid content of the discharged boron nitride composite coating is 25-30%.
Citation Information
Patent Citations
Boron nitride coating for pressure casting and preparation method thereof
CN109848364A
Self-lubricating non-stick molten aluminum environment-friendly coating, coating film and preparation method of self-lubricating non-stick molten aluminum environment-friendly coating
CN111590017A
Full-inorganic non-stick aluminum environment-friendly zirconium silicate coating and preparation method thereof
CN114574009A